Transposition of English Zero Derivation from Nouns to Indonesian Verbs in to Kill a Mockingbird - Hana Fauziah (Bina Nusantara University, 2022)
The research aimed to discuss and analyze the translation of English zero derivation or conversion from nouns to Indonesian verbs using transposition strategy. The research was carried out through the qualitative method by having the constant comparative analysis whose data were collected from Harper Lee’s novel ‘To Kill a Mockingbird’. The data collection was obtained by sampling to support the description based on the classification, including morphological and syntactic categories. The findings show an obvious difference between source and target languages. This occurs when the translation of English zero derivation relies on the affixes more frequently than any other criteria. Furthermore, the overall result proves that the transposition of English conversion from nouns into Indonesian verbs can be analyzed from the verb base that can be converted into nouns, which is then called a deverbal noun, and the noun base that can be converted into a verb. The translation of English zero deverbal noun is possible to be transposed into the target language verb. In a part of formal properties, the identification of English verb base converted into noun could be characterized by the irregular verb, stress pattern, intransitive verb, and semantic complexity, at the same time when the English noun base is transposed into Indonesian verb by considering the verbal interpretation and frequency of occurrence.